2019
DOI: 10.4028/www.scientific.net/kem.812.17
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Impact Force Reconstruction Method for Aerospace Composites

Abstract: This research work presents a hierarchical method able to reconstruct the time history of the impact force on a composite wing stringer-skin panel by using the structural responses measured by a set of surface bonded ultrasonic transducers. Time reversal method was used to identify the impact location by the knowledge of structural responses recorded from a set of excitation points arbitrarily chosen on the plane of the structure. Radial basis function interpolation approach was then used to calculate the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The used RBF interpolation method is explained in detail in [14,15]. In some recent works the authors demonstrated that hierarchical radial basis functions (RBFs) provide high accuracy in the data reconstruction when information related to a point on the structure is not available [11,12]. In the proposed paper, the unknown data are the power values related to the M points on the sample surface, whose known spatial coordinates are the inputs of the RBF interpolation method, in addition to the known N power values to be interpolated and related to the sensor locations.…”
Section: Radial Basis Function Interpolationmentioning
confidence: 99%
See 3 more Smart Citations
“…The used RBF interpolation method is explained in detail in [14,15]. In some recent works the authors demonstrated that hierarchical radial basis functions (RBFs) provide high accuracy in the data reconstruction when information related to a point on the structure is not available [11,12]. In the proposed paper, the unknown data are the power values related to the M points on the sample surface, whose known spatial coordinates are the inputs of the RBF interpolation method, in addition to the known N power values to be interpolated and related to the sensor locations.…”
Section: Radial Basis Function Interpolationmentioning
confidence: 99%
“…𝑃 𝑁 are the power values at 𝑁 transducer locations. As performed in other research works [11,12] the thin plate spline (TPS), whose kernel is πœ™(β€’) = (β€’) 2 𝑙𝑛(β€’), was used as radial basis function for its peculiar characteristics [16].…”
Section: Radial Basis Function Interpolationmentioning
confidence: 99%
See 2 more Smart Citations